Bringing down the house : the crisis in Britain's regional theatres - Turnbull, Olivia (Changing media--changing Europe series., 2008)
Between 1979 and 1997 over a quarter of Britain?s regional theatres closed down. Those that survived found themselves constantly on the brink, forced to reduce their programmes radically and to go dark for extended periods of time. Bringing Down the House delves into how and why this crisis occurred, and examines the long-term effects on Britain?s theatre industry by revealing problems that extend beyond the Conservative government?s scant regard for the arts, right back to the Second World War. By probing the history of regional theatres from the introduction of state funding, Turnbull uneart.